2017
DOI: 10.1111/hae.13295
|View full text |Cite
|
Sign up to set email alerts
|

Desmopressin in haemophilia: The need for a standardised clinical response and individualised test regimen

Abstract: We suggest standardised desmopressin response based on clinically relevant FVIII:C levels, e.g. 0.30 and 0.50 IU/mL. In addition, patients with <0.30 IU/mL FVIII:C after 1 hour (non-responder) or ≥0.80 IU/mL (sustained responder) do not require subsequent blood sampling. However, patients with ≥0.30-0.79 IU/mL FVIII:C after 1 hour should undergo blood sampling after 6 hours to additionally determine response sustainability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Stoof et al suggested incorporating FVIII level at 6‐hour post‐DDAVP administration into the test responsiveness definition. The 1‐hour hr peak FVIII level was used to define non‐responders (<30 IU/dL) and “sustained responders” (≥80 IU/dL).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Stoof et al suggested incorporating FVIII level at 6‐hour post‐DDAVP administration into the test responsiveness definition. The 1‐hour hr peak FVIII level was used to define non‐responders (<30 IU/dL) and “sustained responders” (≥80 IU/dL).…”
Section: Discussionmentioning
confidence: 99%
“…The 1‐hour hr peak FVIII level was used to define non‐responders (<30 IU/dL) and “sustained responders” (≥80 IU/dL). Those with 1‐hour FVIII level 30 to <80 IU/dL were further classified based on the 6‐hour post‐DDAVP FVIII level as “sustained responders” if levels remained ≥30 IU/dL, and “short‐term responder” if levels were <30 IU/dL . The 6‐hour post‐DDAVP FVIII level is a time point selected by Stoof et al for the definition of “sustained responders” based on their testing protocol.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations